PENGARUH DIMESI PELAYANAN TERHADAP KEPUTUSAN PELANGGAN MENGINAP DI HOTEL AMARIS PALEMBANG - Salman .; Nina Fitriana; Rio Herdianto (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACT This study aims to determine the effect of physical tangible, reliability, and responsiveness, assurance, and empathy on the decision of customers staying at the Hotel Amaris Palembang, to analyze the dominant variables affecting the decision customers who stay at Amaris Hotel Palembang, so the analytical method used is multiple linear regression analysis, as well as hypothesis testing consisting of partial tests and simultaneous tests. The results of multiple linear regression analysis showed that the value of sig <0.05. this means that the five dimensions of service (physical evidence, reliability, responsiveness, assurance, empathy) significantly influence customer decisions. From the results of the analysis of the dimensions of service namely physical evidence, reliability, responsiveness, assurance, and empathy show that the dimensions of service provided by Amaris Hotel Palembang can provide decisions to customers, the results of an analysis of the five dimensions of service then the dominant variable affecting customer decisions is assurance ( guarantee). This appears in the value of the regression coefficient = 0.192 and the value of t arithmetic = 3.640 which is greater than the other variables, besides that the smallest value of reliability sig is equal to 0,000. It can be said that the smaller the value of pvalue, the greater the effect on customer decisions. Keywords: Service Dimensions, Customer Decisions